How Alfieri used to read and add notes: the "threshold" annotations between 'extraction' and 'marginalization' (Prassi Ecdotiche della Modernità Letteraria, 2018)
The paper focuses on Alfieri’s annotations in the threshold of the volumes in his possession and aims to consider more generally how he would read and study his books. His habits are in line with the new typographical system and reflect the multiplication of reading practices between the 17th and the 18th centuries (intensive / extensive, silent / aloud reading, extraction / marginalization). Alfieri’s annotations replace, if missing, some elements of the texts, ‘order’ it, and make of its physical support, the book, the point of convergence between the press and the manuscript. On the basis of some examples, we will demonstrate to what extent these annotations offer important information on the working method of Alfieri. Furthermore, we will demonstrate how Alfieri intentionally reorganized his literary archive in order to provide posterity with a confirmation of the reliability of the representation of his literary career already offered in his autobiography, the Vita.
Keywords: Vittorio Alfieri; notes; annotations; author's library; post